A proteasome inhibitor produced by Burkholderia pseudomallei modulates intracellular growth. (June 2017) - Wagley, Sariqa; Vanaporn, Muthita; Rinchai, Darawan; Conejero, Laura; Lertmemongkolchai, Ganjana; Bancroft, Gregory J.; Titball, Richard W.
Abstract: The NRPS/PKS cluster encodes the enzymes necessary for glidobactin synthesis it is partially conserved in various members of the Burkholderia genus including B. pseudomallei . In this study we have shown that the insertional inactivation or deletion of glbC in this cluster in B. pseudomallei could reduce the ability of the bacterium to survive or grow in murine macrophages or in human neutrophils. Exogenously added proteasome inhibitors were able to chemically complement the mutation. The insertional inactivation or deletion of glbC increased virulence in an acute model of infection in Balb/c or C57BL/6 mice but virulence in a chronic model of infection was similar to that of the wild type. Our findings contrast with the previous finding that inactivation of the glb gene cluster in B. pseudomallei strain 1026b resulted in marked attenuation, and provides evidence of differential roles for some genes in virulence of different strains of B. pseudomallei . Highlights: NRPS/PKS cluster encoding the enzymes necessary for glidobactin synthesis is partially conserved in Burkholderia pseudomallei. Inactivation or deletion of glbC reduces the survival or growth in murine macrophages or in human neutrophils. The addition of proteasome inhibitors to the glbC inactivated mutant chemically complemented the mutation. Inactivation or deletion of glbC increased virulence in acute model of infection.